The Country-of-Origin Effect on the Reputation of Russian Metallurgical Products in Central Asian Markets - G. A. Savchuk; V. A. Frants; D. S. Saidmagomedov (Vestnik MGIMO-Universiteta)
The article examines the mutual influence of the country's image and its trading activities in foreign markets. Territorial products are in high demand in other countries and connected in the minds of consumers with the country of production. The authors focus their attention on Central Asia as a region with an actively developing economy and essential for Russia in building the Eurasian Economic Union (EAEU). There is also a high interest in this region from other countries – the USA, China, Turkey, South Korea, Japan. The article analyzes whether Russian metallurgical products can be considered a territorial product that increases the country's attractiveness as a whole in the market of Central Asian countries. The study aims to compare consumers' attitudes to Russian and Chinese metal products, as Chinese metal producers are currently becoming more active in the market of Central Asian countries. The study employs two methods: an expert interview and a survey of consumers of metallurgical products.The authors conclude that Russian metallurgical products have a stable positive reputation in the market of Central Asian countries. Its reputation in the minds of consumers is associated not only with the price and quality of the product itself but also with a high level of metallurgical education and research and production activities in Russia. In addition, it is essential for consumers that product information is presented in a familiar language, and the cultural features of business communication of Russian suppliers are close and understandable to them. In turn, Chinese metallurgical products do not have such a reputation since Central Asian consumers do not have experience in its utilization, are not aware of the history of metallurgical production in China, scientific and technical developments, and the quality of professional education in the field of metallurgy in this country. They also do not understand China's language and business culture; they are not familiar enough with Chinese suppliers, which affects their choice in favor of a Russian supplier. On this basis, the authors conclude that Russian metallurgical products can be considered a territorial product in the market of Central Asian countries.